Customer requirements and the quality improvement of health care services - Ludwiczak Anna (Management, 2016)
Customer oriented approach is at present the most important principle in quality management. It becomes particularly significant in the context of offering the society high standard health care services. The aim of the research presented in the paper is to diagnose the functioning of customer oriented approach in Polish hospitals, and in particular actions in respect of meeting customer requirements at the stage of developing and improving health care services. Additional the paper attempts to identify the barriers preventing the inclusion of customer requirements in the process of improvement of health care services. The first paper of the paper presents the essence of customer orientation and defines basic concepts in the context of health care services. Next selected concepts in quality oriented approaches directed at customers are analyzed. The subsequent chapter includes the results of empirical research concerning the application of solutions oriented on the improvement of health care services in the sphere of increasing customer satisfaction in hospital in the Lubuskie Province. In summary, the results of the research are discussed and directions for further research identified.